Poems of home: domestic poetry written by Antonio Rubino and Emilia Villoresi - Surdi, Elena (Rivista di Storia dell’Educazione, 2020)
In the preface Della poesia domestica. Pensieri (“On domestic poetry. Thoughts”) (1839) Giulio Carcano outlines a connection between poetry and family life. The author believes that home and intimate relationships are by nature rife with poetry. In Poetry for childhood in the XIX Century (“Poesia per l’infanzia nel sec. XIX”) (2007) Renata Lollo unlocks the educational potential of this vision. The paper, leveraging on this hermeneutical vision, proposes domestic poetry as a the interpretative lense to analyze some works by Antonio Rubino (1880-1964) and Emilia Villoresi (1892-1979). On the Corriere dei Piccoli, between 1909 and 1934 Rubino published several components based on the daily life for a child at the time. The artist, capable of adopting a multimedial approach in his dialogue with childhood, always considered poetry as the optimal way to narrate and to educate to beauty. By describing in verses daily life and domestic chilhood life he unlocks all its depth and richness. Likewise in 1937 Emilia Villoresi published Picci, non far capricci, a collection of poems dedicated to her niece that narrate the life of a three year old child. The poems describe simple and funny life episodes and, through rime, they are conveyed to children through images they are familiar with, using a clear but fascinating language. For both authors poetry is a primary choice used to describe childhood and to addreess childhood, full of educational meanings. By dealing with apparently trivial issues (linked to domestic and everyday life), poetry makes literature available to the youngest and educates them to the values that are pillars of family life.